Influência das estratégias de ensino e dos estilos cognitivos no desenvolvimento de objetos digitais de aprendizagem - Silva, Arthur Ribeiro Assunção da (Universidade Federal Rural do Semi-Árido, 2018)
The use of digital technologies in the teaching-learning process is increasingly being discussed, therefore, it is even more important to understand the reliability of such methods. The present study aims to identify the benefits of using Digital Learning Objects in a school, involving the collaboration of students and teachers. The latter applied a DLO in the classroom to facilitate the study of science approaching the theme of water. The research is based on a case study with bibliographic depth in published studies on Learning Theories, Cognitive Styles and Digital Learning Objects. The evaluated class attends the sixth year of the elementary school of a local public school, and used an DLO that provided video lesson, quizz games, texts and interactive images. All of them underwent an evaluation after using the DLO. And although the school where the study was applied did not carry technological devices introduced in the context of the classes with a certain periodicity, we identified an improvement in the class performance. According to the analysis, the data showed the importance of using this technology in the teaching-learning process. It is believed that the best learning occurs when built in a playful and interactive environment that enables the perceptions to stimulate the intellect of each student through involvement and proficiency.
Monografia
Keywords: Objetos digitais de aprendizagem; Estilos Cognitivos; Teorias de aprendizagem; Ensino-aprendizagem; Digital learning objects; Cognitive styles; Learning theories; Teaching-learning; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA